DILEMA EUTHANASIA PERSPEKTIF ETIKA ILMU PENGETAHUAN - Fadlullah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
Human life that has continued for thousands of years continues to experience developments a nd dynamics, especially in the scientific field. Humans need something to support their survival, which is then called science. History of science has received great attention, because with this knowledge, humans are able to become civilized beings than ot her creatures in this world. In the development of science, of course there are many problems that intersect with various aspects of human life, such as social, cultural and religious. To maintain good relations between science and various aspects of human life, ethics are needed. Ethics as control over the development of science. This is what we deserve to address in the issue of Euthanasia from a scientific ethics point of view.